The Role of Management Information Systems in Developing Job Performance: A filed Study on Employees at Arabian Yemen Cement Company Limited - Belhaj, Fawzi Ali; Bin Kulaib, Mohsen Mohammed (Journal of Economic, Administrative and Legal Sciences, 2019)
The purpose of study is to examine the role of management information Systems (MIS) in developing job performance of employees who work in Arabian Yemen Cement Company Limited in Mukalla. In addition, to explore the situation of management information systems in the company, and the obstacles that may hinder system application effectively. The study population was (453) employees in the company. The data was collected through a questionnaire by using a simple random sample of (120) employees from different levels who involved in management information systems. (150) questionnaires were distributed and the response rate was (80%). The key findings indicate that, there is a major role of management information systems on developing job performance in the company. Furthermore, there is high and positive awareness toward management information systems situation in the company and there are no difficulties affecting the application of management information systems. It is recommended that the company should introduce flexibility and continuous development to enhance the role of management information systems in performance. Future researches should be carried out on the influence of management information systems on organizational performance in private and public sectors in different environments.